PEDAGOGICAL CULTURE AS AN IMPORTANT FACTOR OF PROFESSIONAL COMPETENCE OF THE FUTURE TEACHER OF TECHNOLOGY (Pedagogy of Higher and Secondary Education, 2022)
In the article problems of definition of criteria of an estimation of levels of formation of professional – pedagogical culture of the teacher of initial classes are considered. The analysis of the pedagogical literature problem of professional and pedagogical culture carried out, criteria of professional – pedagogical culture  of students are determined.
Keywords: professional-pedagogical culture; culture; pedagogical culture